1923 Conn. Pub. Acts 3707 - (:unkn) unknown (My University, 1923)
An Act Concerning the Possession, Sale and Use of Pistols and Revolvers, ch. 252, § 3Required a license from the chief of police for the retail sale of pistols and revolvers. Also granted the superintendent of the state police a "may issue" permitting scheme.
Keywords: LICENSE - DEALERS